2011
DOI: 10.1111/j.1540-8167.2011.02199.x
|View full text |Cite
|
Sign up to set email alerts
|

Head‐To‐Head Comparison of Arrhythmia Discrimination Performance of Subcutaneous and Transvenous ICD Arrhythmia Detection Algorithms: The START Study

Abstract: Appropriate ventricular arrhythmia detection is excellent for all ICD systems evaluated; however, specificity of supraventricular arrhythmia discrimination by the S-ICD system is better than discrimination by 2 of 3 TV systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
135
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 193 publications
(141 citation statements)
references
References 28 publications
3
135
0
3
Order By: Relevance
“…When programmed to include a conditional shock zone, the S-ICD VT detection algorithm has been demonstrated to be more effective than transvenous ICD systems programmed at nominal settings to prevent the detection of induced supraventricular arrhythmias [153]. Furthermore, in the clinical evaluation of the conditional shock zone, the S-ICD system was strongly associated with a reduction in inappropriate shocks from supraventricular arrhythmias and did not result in prolongation of detection times or increased syncope [154].…”
Section: The Subcutaneous Defibrillator (S-icd)mentioning
confidence: 99%
“…When programmed to include a conditional shock zone, the S-ICD VT detection algorithm has been demonstrated to be more effective than transvenous ICD systems programmed at nominal settings to prevent the detection of induced supraventricular arrhythmias [153]. Furthermore, in the clinical evaluation of the conditional shock zone, the S-ICD system was strongly associated with a reduction in inappropriate shocks from supraventricular arrhythmias and did not result in prolongation of detection times or increased syncope [154].…”
Section: The Subcutaneous Defibrillator (S-icd)mentioning
confidence: 99%
“…Around 8% of S-ICD patients receive inappropriate therapy and this is mainly due to oversensing. 11 This rate is comparable to present TV-ICD systems and can be substantially and safely reduced with appropriate device programming. 12 The S-ICD requires greater defibrillation energy (80 Joules) than a TV-ICD (35 Joules).…”
mentioning
confidence: 53%
“…The START study [2] compared the ability of S-ICD with single chamber and dual chamber transvenous ICD to sense arrhythmias induced during programmed electrophysiological testing in 64 patients. This demonstrated that the S-ICD specificity in discriminating supraventricular arrhythmias was superior to transvenous systems (98.0% vs. 68.0% p<0.001).…”
Section: Discussionmentioning
confidence: 99%